Perspectives of older people living in long-term care facilities and of their family members toward advance care planning discussions: a systematic review and thematic synthesis - Mignani V (Dove Medical Press, 2017)
Veronica Mignani,1 Francesca Ingravallo,1 Elena Mariani,2 Rabih Chattat2 1Department of Medical and Surgical Sciences, University of Bologna, Via Irnerio, Bologna, Italy; 2Department of Psychology, University of Bologna, Viale Berti Pichat, Bologna, Italy Objective: We aimed to search and synthesize qualitative studies exploring the perspectives of older people living in long-term care facilities and of their family members about advance care planning (ACP) discussions. Methods: The enhancing transparency in reporting the synthesis of qualitative research (ENTREQ) framework was used to guide the review and report its results. PubMed, CINAHL, and PsycINFO were searched for studies published between January 2000 and November 2015. All included studies were assessed for comprehensiveness of reporting, and a thematic synthesis of their results was performed. Results: The nine included studies differed in terms of qualitative method used, comprehensiveness of reporting, and geographical origin. The thematic synthesis led to the identification of four main themes: 1) plans already made; 2) end-of-life care and decision-making; 3) opinions and attitudes toward ACP; and 4) how, when, about what, and with whom to do ACP. Conclusion: Despite their willingness to be involved in a shared decision-making process, older residents and their families still have little experience with ACP. Practical implications: In view of implementing ACP for elders living in long-term care facilities, it would be important to rethink ACP and also to incorporate their nonmedical preferences, according to their own priorities. Keywords: advance care planning, frail elderly, caregivers, residential facilities, qualitative research